Pyruvate metabolism by aminopterin-inhibited Aerobacter aerogenes - Webb, M. (1968)
1. The synthesis and utilization of both alanine (by reductive amination, oxidative deamination and transamination) and valine (by transamination only) in Aerobacter aerogenes are unaffected by aminopterin. These amino acids, which accumulate in aminopterin-treated cultures of this organism, are therefore considered to be formed as secondary products from the excess of pyruvate that also accumulates. 2. Oxidative metabolism of pyruvate and the synthesis of acetylmethylcarbinol by A. aerogenes cells are unaltered by growth in the presence of aminopterin. 3. Cells from static and anaerobic cultures that have been treated with the folic acid antagonist in the early exponential phase have a decreased ability to cleave pyruvate to acetate and formate, and to effect the exchange of formate with the carboxyl group of pyruvate. 4. 3-Methyl-2-oxobutanoate, the keto acid precursor of valine, cannot replace pyruvate as substrate in either the phosphoroclastic or the exchange reaction.